The Economic Factors Influencing Exchange Rate of Kip (LAK) against Yuan (CNY): https://doi.org/10.69692/SUJMRD080288 - SOMSACKXAYSOMPHENG , Oulavieng; PHENGSAVAT, Sitthivikone; NORCHANDA, Sithone; NOUANTHASING , Kommaly; XAYAVONG, Somkhuan (Souphanouvong University Journal Multidisciplinary Research and Development, 2022)
This research aimed to investigate the economic factors that influence the exchange rate of LAK against the CNY. The researchers used the quarterly data from the database of the Bank of Lao. PDR and Bank of Chaina in the period of 2015-2020 (24 quarters) by testing the economic factors influencing the exchange rate of LAK against CNY in the long-term period by applying the Engle and Grenger method and the short-term period through the Error Correction Model. The results found that the fluctuation in exchange rate of LAK against CNY in long-term was positively influenced by the economic factors, which consisted of 4 factors as: 1) the change of money supply differential, which LAK appreciated against CNY, 2) the change of inter-bank rate differential, which LAK depreciated against CNY 3) the change of export differential, which LAK appreciated against CNY and 4) the change of comparative consumer price index differential, which LAK depreciated against CNY. The results of the fluctuation in exchange rate of LAK against CNY in short-term was positively influenced by the economic factors, which consisted of 3 factors as: 1) the change of money supply differential, which LAK appreciated against CNY; 2) the change of inter-bank rate differential, which LAK depreciated against CNY and 3) the change of export differential, which LAK appreciated against CNY.